Problem-Oriented Learning Family Models on Decision-Making Skills in Indonesia - Umalihayati; Fajari, Laksmi Evasufi Widi; Hidayah, Ratna; Rahmadani, Kurniati; Sari, Novita (Universitas Pendidikan Ganesha, 2025)
Decision-making skills are an essential competency in education but remain challenging to develop effectively through problem-based learning models in Indonesia. This study aims to analyze the significant influence of problem-based learning models on decision-making skills in Indonesia using a meta-analytic approach. The research method employed is quantitative meta-analysis. The eligibility criteria include: (1) relevant topics; (2) empirical research results; (3) availability of (r), (t), or (F) values; (4) sample size N ≥ 20; (5) use of internationally recognized language; (6) indexed in Scopus, Web of Science, or SINTA; and (7) accessible through national and international journal databases. Data analysis techniques involved statistical methods to test heterogeneity, calculate effect size, and assess publication bias using JASP software version 18.3.0. The results showed: (1) significant heterogeneity in the heterogeneity test; (2) the summary effect size test revealed an intercept value of 0.814, categorized as a very strong effect; (3) no potential publication bias was detected. This study concludes that problem-based learning family models have a strong influence on decision-making skills in Indonesia. The findings of this study imply the importance of integrating problem-based learning models into the national curriculum and strengthening teacher training to effectively enhance students’ decision-making skills in Indonesia.